2019
DOI: 10.1002/tcr.201800169
|View full text |Cite
|
Sign up to set email alerts
|

Surface Compositions of Oxide Supported Bimetallic Catalysts: A Compared Study by High‐Sensitivity Low Energy Ion Scattering Spectroscopy and X‐Ray Photoemission Spectroscopy

Abstract: It is well known that there is a critical relationship between the surface composition and catalytic performance for a bimetallic catalyst. However, in most cases, the surface composition is obviously different from that of the bulk. Moreover, the surface is normally reconstructed under reaction conditions. In this personal account, our recent progresses in determining the surface compositions of oxide supported bimetal catalysts by high‐sensitivity low energy ion scattering spectroscopy (HS‐LEIS) and X‐ray ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…For Pd/CeO 2 , the binding energy of Pd 3d5/2 is about 337.4 eV after oxidation at 400 °C (Figure S4), which is higher than the typical values of the bulk PdO, for example, 336.6 eV for Pd-Au/TiO 2 and 337 eV for Pd/TiO 2 . 30 The difference of Pd 3d5/2 between the oxidized and reduced Pd/CeO 2 is 2 eV, which is close to those of the above-mentioned Pd/TiO 2 catalysts. Moreover, the Pd 3d5/2 for Pd 2+ in the PdCeO x solid solution was reported to be 338 eV.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…For Pd/CeO 2 , the binding energy of Pd 3d5/2 is about 337.4 eV after oxidation at 400 °C (Figure S4), which is higher than the typical values of the bulk PdO, for example, 336.6 eV for Pd-Au/TiO 2 and 337 eV for Pd/TiO 2 . 30 The difference of Pd 3d5/2 between the oxidized and reduced Pd/CeO 2 is 2 eV, which is close to those of the above-mentioned Pd/TiO 2 catalysts. Moreover, the Pd 3d5/2 for Pd 2+ in the PdCeO x solid solution was reported to be 338 eV.…”
Section: Resultssupporting
confidence: 76%
“…Surface-sensitive characterizations were mainly performed with high-sensitivity low-energy ion scattering spectroscopy (HS-LEIS) and X-ray photoelectron spectroscopy (XPS) combined with a homemade ambient pressure ex-situ reaction cell, and more details have been reported previously. , The catalysts were pretreated in an ex-situ continuous-flow reactor under atmospheric pressure, which can mimic the experimental conditions to be the same as the realistic reaction enviornment. Oxidation and reduction treatments were conducted with 20 vol % O 2 /N 2 and H 2 (99.999%).…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that the In concentration near the surface layers can be increased by increasing the In loading in the catalyst. This phenomenon was also observed in a range of bimetallic materials, intermetallic compounds, and transition metal ceramics. , …”
Section: Results and Discussionmentioning
confidence: 98%